ANCIENT MUSICAL INSTRUMENTS AND THEIR TYPES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The role of playing national musical instruments in Uzbek music is incomparable. Effective use of them gives us many opportunities. We need to improve their quality, perfect performance, and in order to perform them perfectly, we need to pay special attention to their quality. They have been reworked and developed by many specialists, who have expanded their performance possibilities even more. This led to a more perfect performance of our national songs.